Interference of alkaloids with neuroreceptors and ion channels - Wink, Michael (Bioactive natural products, 2007)
Alkaloids represent one of the largest classes of natural products produced not only by plants but also by marine animals and amphibia, certain bacteria and fungi. Their general function in plants and animals seems to be chemical defence against herbivorous and predating animals. In order to fulfil this function alkaloids had to be shaped during evolution (by a process termed “evolutionary molecular modelling”) in such a way that they can interfere with important molecular targets of animals. Neuronal signal transduction, especially interference with neuroreceptors, enzymes of neurotransmitter metabolism and signal transduction, and with ion channels represent such animal specific targets. This review summarizes the experimental data on the molecular interactions of more than 300 alkaloids with neuroreceptors and ion channels and interprets these results under evolutionary and applied aspects, such as their exploitation as medicinal compounds or biorational pesticides for agriculture.